The role of clostridia in Bantu beer fermentations - Ihlenfeldt, Michael Jürgen Alexander; Ihlenfeldt, Michael Jürgen Alexander (Department of Molecular and Cell Biology, 2017)
1. The occurrence of clostridia in various stages of Bantu beer production was investigated in order to determine their significance as spoilage organisms in the brewing process and in the final product. 2. The ecology of clostridia was studied by investigating the selective factors of the environment according to the concepts of Beijerinck and Baas Becking. This study was extended by quantitative investigations of the microbial population according to the approach of Hungate. 3. A new modification of existing techniques for the enumeration of clostridia is described. 4. Although clostridia were found to occur as part of the normal flora of brewing ingredients and could be detected in all stages of the normal brewing process, they were present in spore-form only. It was found that the environmental factors were not favourable for their growth. 5. The conditions under which clostridia could occur are discussed. 6. The strains isolated in this study were grouped using a distance coefficient on the University of Cape Town ICT 1303 computer. 7. The significance of the two groups that emerged from the numerical study is discussed in relation to the microbial species problem as a whole.